Modal Auxiliary Video as Learning Media For 11th Grade of Senior High School - Al-Husna, Nayla Zahroh; Nur, Luluk Choirun Nisak; Hidayat, Rohmat (Universitas KH. A. Wahab Hasbullah, 2023)
This research is aimed to design an English learning media, Modal Auxiliary Learning Video based on a video to facilitate the 11th Grade student of MA Al-I’dadiyyah Bahrul Ulum in learning Modal Auxiliary. In designing the Modal Auxiliary Learning Video for the 11th Grade of Senior High School, the researchers applied Research and Development (R&D) method which is including a specific research model ADDIE. The instruments which are used in collecting the data are interview and questionnaire. The result of material validation achieved 63% score percentages which means the media is worth to be tried out with revision. The media validation achieved 82% score percentages which means the media is strongly worth to be tried out with no revision after being revised and implemented on the students, the final result on the implementation stage was 95% and categorized as “Very Good” category. Based on the results above, the Modal Auxiliary Learning Video for the 11th Grade of Senior High School can be concluded as a feasible and appropriate media to be used for the 11th Grade of Senior High School in learning English, especially in the term of Modal Auxiliary.